Master tracks in different resolutions of METEOR cruise M207, Belem - Mindelo, 2025-01-04 - 2025-02-11 - Rebecca Hummels (PANGAEA, 2025)
Raw data acquired by position sensors on board RV METEOR during expedition M207 were processed to receive a validated master track which can be used as reference of further expedition data. During M207 the motion reference unit Kongsberg SeaTex AS MRU-5 combined with Kongsberg SeaTex AS Seapath 320 and two C and C Technologies GPS receivers C-NAV3050 were used as navigation sensors. Data were downloaded from DAVIS SHIP data base (https://dship.bsh.de) with a resolution of 1 sec. Processing and evaluation of the data is outlined in the data processing report. Processed data are provided as a master track with 1 sec resolution derived from the position sensors extquotesingle data selected by priority and a generalized track with a reduced set of the most significant positions of the master track.